2018
DOI: 10.3390/su10114327
|View full text |Cite
|
Sign up to set email alerts
|

A Microeconomic Methodology to Evaluate Energy Efficiency by Consumption Behaviors and Strategies to Improve Energy Efficiency

Abstract: The present paper highlights a quantitative method to maximize energy efficiency based on the minimum energy consumption and maximum quality of life from consumption behaviors. Quality of life is expressed by utility, which is a Constant Elasticity of Substitution (CES) function of demands for composite goods, car trips and public transport trips. Individual energy consumption is estimated by the demand of goods and we applied this method to Nagasaki to evaluate energy efficiency. Our results showed that 28,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The result showed that it is significant to allocate appropriate slack time to provide effective flexible line service. Dijosephl et al [37][38][39] developed an optimization algorithm to search for the maximal-profits optimal solution by considering the public transport network and passenger demand, as well as optimized the regional public transport system and financially sustainable operation.…”
Section: Coordination and Optimization Of Rail And Public Transportmentioning
confidence: 99%
“…The result showed that it is significant to allocate appropriate slack time to provide effective flexible line service. Dijosephl et al [37][38][39] developed an optimization algorithm to search for the maximal-profits optimal solution by considering the public transport network and passenger demand, as well as optimized the regional public transport system and financially sustainable operation.…”
Section: Coordination and Optimization Of Rail And Public Transportmentioning
confidence: 99%